Answer:
The equations are given below as
![\begin{gathered} 3a+4b+2c=11\ldots\ldots(1) \\ 2a+3b-c=4\ldots\text{.}(2) \\ 5a+5b-3c=-1\ldots..(3) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/pp1g8ar6hk5yc9qi90lsqydazl2zprzq37.png)
Step 1:
Multiply equation 1 by 2 and multiply equation 2 by 3
![\begin{gathered} 2(3a+4b+2c)=11*2 \\ 6a+8b+4c=22\ldots\text{.}(4) \\ 3(2a+3b-c))=4*3 \\ 6a+9b-3c=12\ldots\text{.}(5) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/uqvxo4ezfqslzzb3r1ossdfgelrfq13tnd.png)
Step 2:
Substract equation 4 from 5
![\begin{gathered} 6a-6a+9b-8b-3c-4c=12-22 \\ b-7c=-10\ldots\text{.}(6) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/jhsnqjzts84jci14dbeq4djszbdrfe4alu.png)
Step 3:
Multiply equation (2) by 5 and then equation 3 by 3
![\begin{gathered} 5(2a+3b-c)=4*5 \\ 10a+15b-5c=20\ldots\ldots(7) \\ 2(5a+5b-3c)=-1*2 \\ 10a+10b-6c=-2\ldots\text{.}(8) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/n2ksmkq0zq2umklvn6t7jawrcvh8g0q077.png)
Step 4:
Substract equation (8) from equation (7)
![\begin{gathered} 10a-10a+15b-10b-5c+6c=20+2 \\ 5b+c=22\ldots\ldots(9) \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/4e6myoaawudxm2e5pqj95vzdd1mw87livw.png)
Step 5:
From equation (9)
![c=22-5b\ldots\text{.}(10)](https://img.qammunity.org/2023/formulas/mathematics/college/k5p9i46spk5oso4wr64iihv51uocg0fzug.png)
Substitute equation 10 in equation (6)
![\begin{gathered} b-7c=-10 \\ b-7(22-5b)=-10 \\ b-154+35b=-10 \\ 36b=-10+154 \\ 36b=144 \\ (36b)/(36)=(144)/(36) \\ b=4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6ez4okkp9v0kgkjxbavhgeni0qn7o05kmf.png)
Step 6:
Substitute the value of b=4 in equation (10)
![\begin{gathered} c=22-5b \\ c=22-5(4) \\ c=22-20 \\ c=2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ti1gjhl3l7in0x6lvvb658kndqndjm4b3j.png)
Step 7:
Substitute c=2 and b=4 in equation (2)
![\begin{gathered} 2a+3b-c=4 \\ 2a+3(4)-2=4 \\ 2a+12-2=4 \\ 2a+10=4 \\ 2a=4-10 \\ 2a=-6 \\ (2a)/(2)=-(6)/(2) \\ a=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ibpy9vzh62csyl79c0m9lm6ym3dcqwho6j.png)
Hence,
a =-3 , b=4 , c=2
OPTION C is the right answer